A Review on the Manuscript of Turkish Quran YWJ68197MSI.4 in Database Management System (DBMS) - Kadir, Mohd Nazir; Azmi, Riswadi; Mohd Saad, Mohd Faizulamri; Zainol, Nur Zainatul Nadra; Mohd Yunus, Mohd Amin (Journal of Quranic Sciences and Research, 2021)
The writingsofthe Quran has begun since the time of the Prophet (PBUH) and it has continued until today. It has been proven that here are manuscripts of the Quran around the world that are handwrintten. The Quran manuscripts of the great works are so meticulous and scattered around the world. The writing activity or the so-called copying is carried out on the basis of honor to the kalam AllÄh. Thus, the preliminary study is conducted on a Turkish Quran manuscript written by Hasan Husni. The manuscript is a collection of Yayasan Warisan Johor (YWJ), Johor Bahru. However, there is no computerized system for saving the manuscript proper manner and secured electronically as well as may be referred and retrieved in the future.The purpose of this study is to find out the method of writing al-Quran based on the focus on knowledge of rasm, marking (dhabt al-Quran), fawasil, forms of illumination and calligraphy and saved in database management system (DBMS) properly with authentication. In addition, it is intended to highlight YWJ's contribution in preserving the manuscripts of the Quran in the state of Johor. This study isa qualitative method using content analysis approach. The findings show that the Turkish manuscripts contain very beautiful local features and further studies should be conducted specifically on the perspectives of the Quran.